2022
DOI: 10.1007/s00018-022-04539-0
|View full text |Cite
|
Sign up to set email alerts
|

Heterocomplexes between the atypical chemokine MIF and the CXC-motif chemokine CXCL4L1 regulate inflammation and thrombus formation

Abstract: To fulfil its orchestration of immune cell trafficking, a network of chemokines and receptors developed that capitalizes on specificity, redundancy, and functional selectivity. The discovery of heteromeric interactions in the chemokine interactome has expanded the complexity within this network. Moreover, some inflammatory mediators, not structurally linked to classical chemokines, bind to chemokine receptors and behave as atypical chemokines (ACKs). We identified macrophage migration inhibitory factor (MIF) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 84 publications
(134 reference statements)
0
5
0
Order By: Relevance
“…In addition to its direct effects on inflammation and plaque stability, MIF interacts intricately with CXCL4L1, leading to the formation of prothrombotic and proinflammatory MIF-CXCL4L1 heterocomplexes ( 47 , 48 ). These heterocomplexes have been implicated in promoting endothelial dysfunction, thrombosis, and exacerbation of inflammatory responses within the vascular environment ( 49 ). The presence of the -173 polymorphism in the MIF gene may modulate the formation or activity of these heterocomplexes, potentially influencing the progression and severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its direct effects on inflammation and plaque stability, MIF interacts intricately with CXCL4L1, leading to the formation of prothrombotic and proinflammatory MIF-CXCL4L1 heterocomplexes ( 47 , 48 ). These heterocomplexes have been implicated in promoting endothelial dysfunction, thrombosis, and exacerbation of inflammatory responses within the vascular environment ( 49 ). The presence of the -173 polymorphism in the MIF gene may modulate the formation or activity of these heterocomplexes, potentially influencing the progression and severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of PF4V1 observed in the present study using the influenza HA antigen and the same adjuvant suggests that the PF4V1 induction is not antigen-specific but related to the inflammatory effect of the Poly(I:C) adjuvant. Brandhofer et al reported that PF4V1 forms a heterocomplex with an atypical chemokine macrophage migration inhibitory factor (MIF) and that the PF4V1-MIF complex does not have chemotactic activity to T cells and monocytes [49]. The upregulation of PF4V1 may have a suppressive aspect for inflammation caused by adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the formation of the CXCL4/CCL5 heterodimer was validated experimentally both in vitro and in vivo [ 5 , 6 ]. More recently, Brandhofer et al [ 55 ] demonstrated that heterocomplexes also form between atypical chemokine MIF (macrophage migration inhibitory factor) and CXCL4L1 and regulate inflammation and thrombus formation in patients with peripheral artery disease.…”
Section: Chemokinesmentioning
confidence: 99%